A putatively phase variable gene (dca) required for natural competence in Neisseria gonorrhoeae but not Neisseria meningitidis is located within the division cell wall (dcw) gene cluster. - Snyder, L; Saunders, N; Shafer, WM (2001)
A cluster of 18 open reading frames (ORFs), 15 of which are homologous to genes involved in division and cell wall synthesis, has been identified in Neisseria gonorrhoeae and Neisseria meningitidis. The three additional ORFs, internal to the dcw cluster, are not homologous to dcw-related genes present in other bacterial species. Analysis of the N. meningitidis strain MC58 genome for foreign DNA suggests that these additional ORFs have not been acquired by recent horizontal exchange, indicating that they are a long-standing, integral part of the neisserial dcw gene cluster. Reverse transcription-PCR analysis of RNA extracted from N. gonorrhoeae strain FA19 confirmed that all three ORFs are transcribed in gonococci. One of these ORFs (dca, for division cluster competence associated), located between murE and murF, was studied in detail and found to be essential for competence in the gonococcal but not in the meningococcal strains tested. Computer analysis predicts that dca encodes an inner membrane protein similar to hypothetical proteins produced by other gram-negative bacteria. In some meningococcal strains dca is prematurely terminated following a homopolymeric tract of G's, the length of which differs between isolates of N. meningitidis, suggesting that dca is phase variable in this species. A deletion and insertional mutation was made in the dca gene of N. gonorrhoeae strain FA19 and N. meningitidis strain NMB. This mutation abrogated the ability of the gonococci to be transformed with chromosomal DNA. Thus, we conclude that the dca-encoded gene product is an essential competence factor for gonococci.